(untitled) (Research, Society and Development, 2021)
COVID-19 has spread throughout the world due to an exponential growth in the number of cases, having been declared by the WHO as a pandemic in March 2020. Among the different mechanisms to face the challenges posed by the pandemic, health professionals have spirituality and religiosity as support in coping with situations of uncertainty and adversity, the binomial being a source of comfort and understanding. The incidence of spirituality among health professionals who work on the front line of confronting COVID-19 was verified in a municipality in the southwest of Bahia and its correlation with quality of life, fear of COVID and the development of mild mental disorders. This is a cross-sectional, descriptive study with a quantitative approach, carried out among 152 professionals. Socio-economic-demographic conditions were assessed using a questionnaire previously prepared by the researchers, the variable spirituality, religiosity and personal beliefs assessed through the application of the WHOQOL-SRBP instrument, the variables common mental disorders, quality of life and fear of COVID were investigated, respectively, through the QSG, SF-12 and Fear of COVID. Data were submitted to descriptive and bivariate analysis using Spearman’s rank correlation coefficient. 147 professionals answered the study questionnaires (96.71%), highlighting the scores presented by the WHOQOL-SRBP, between 48 and 127, CI [99.07;105.01] and by the QSG, 9 and 36, CI [20.72;24.35]. It was concluded that spirituality is related to a lower rate of common mental disorders and a higher quality of life.